2014
DOI: 10.1128/aem.02006-14
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Non-Mucus-Adherent Derivatives of Lactobacillus rhamnosus GG Reveals Genes Affecting Pilus Biogenesis

Abstract: c Lactobacillus rhamnosus GG is one of the best-characterized lactic acid bacteria and can be considered a probiotic paradigm. Comparative and functional genome analysis showed that L. rhamnosus GG harbors a genomic island including the spaCBAsrtC1 gene cluster, encoding the cell surface-decorating host-interacting pili. Here, induced mutagenesis was used to study pilus biogenesis in L. rhamnosus GG. A combination of two powerful approaches, mutation selection and next-generation sequencing, was applied to L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(54 citation statements)
references
References 36 publications
(48 reference statements)
4
49
1
Order By: Relevance
“…Mucus-binding assays of the three L. rhamnosus isolates (N1, N3, and N8), the pilus-negative strain PB12 (16), and the reference strain GG were carried out, as described previously (16). The relative binding capacities of N1, N3, N8, and PB12 were calculated compared to the capacity of the reference strain GG.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mucus-binding assays of the three L. rhamnosus isolates (N1, N3, and N8), the pilus-negative strain PB12 (16), and the reference strain GG were carried out, as described previously (16). The relative binding capacities of N1, N3, N8, and PB12 were calculated compared to the capacity of the reference strain GG.…”
Section: Methodsmentioning
confidence: 99%
“…Excluding the acquisition of foreign mobile DNA, such as plasmids, conjugative transposons, or phages, bacterial genomes would mostly evolve through the loss, decay, or duplication of genes that result from either small mutational events, i.e., single nucleotide polymorphisms (SNPs) and insertions/deletions (indels), or larger genomic rearrangement events that are typically mediated by insertion sequence (IS) elements. In addition to causing large chromosomal deletions or inversions (15,16), IS elements can also have some more localized impacts on coding capacities and gene expression by inactivating or activating gene(s) (17). Thus, we identified that the activation of the pilus gene cluster spaCBA-srtC1 was caused by the insertion of an iso-IS30 element that created an active and constitutive promoter upstream of the spaC gene, from which we determined the transcriptional start site experimentally (18).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They also have the ability to bind to the mucus, through the presence of the subunit SpaC mucus binding domain (Kankainen et al, 2009;Reunanen et al, 2012). Another factor differentiating ability of individual strains to adhere to the intestinal epithelium are variations in the sequences encoding the fi mbrial protein structure (Toh et al, 2013) and its expression Rasinkangas et al, 2014). The spaCBA complete coding sequence is present in L. paracasei DS6 and L. casei DS8 isolates but the protein is not expressed (Markowicz et al, 2014).…”
Section: Analysis Of the Phylogenetic Relationship Between Tested Isomentioning
confidence: 99%